Endowment effect theory, prediction bias and publicly provided goods – an experimental study - Ivo Bischoff (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2006)
Many studies report on a systematic disparity between the willingness to pay for a certain good (WTP) and the willingness to accept retribution payments in exchange for giving up this good (WTA). Thaler (1980) employs prospect theory to explain this disparity. The literature contains two different interpretations of his endowment effect theory. Accordingly, the disparity is caused either by the disutility from parting with one's endowment and/or by an extra utility from ownership which is not anticipated by individuals who are not endowed with the good. So far, the empirical evidence on the applicability of endowment effect theory is limited to private goods. The current paper reports on an experiment which finds a significant ownership utility effect for a publicly provided good. This result indicates that prospect theory applies to publicly provided goods even though consumers do not have exclusive property rights.
Keywords: H40; C92; Q51; H43; 330; endowment effect; loss aversion; publicly provided goods; experiment